Experimental Testing Results of Reinforced Concrete Beams Under Biaxial Bending - Pavlikov, Andriy; Kosior-Kazberuk, Marta; Harkava, Olha (International Journal of Engineering and Technology, 2018)
The experimental tests data of reinforced concrete beams of a rectangular profile made of heavy concrete on pure biaxial bending are presented. The inclination angle of the external load plane to the vertical axis of inertia of the section varied in the range from 0Âº to 20Âº. The tests were conducted to study the work of the biaxial bended elements under load and to verify the developed method for strength analysis of such elements. It has been established that the order of changing the neutral axis position in the section of the biaxial bending beams in the loading process depends primarily on the relative disposition of the external load plane and the resultant in the tensioned reinforcement. It has been confirmed that the ultimate compressed fibrous strains of concrete depend not on the shape of the section, but on the shape of the concrete compressed zone. The results of the tests have good correspondence with theoretical calculations, which proves the expediency of using the developed engineering method for the strength analysis.Â Â